ANALYSIS OF ANTHROPOMETRIC CHARACTERISTICS OF YOUNG MEN STUDYING AT A SPECIALIZED LYCEUM - Khankeldiev Sh.H; H. B .Abidov (Journals Park Publishing, 2022)
The article presents the results of experimental studies to identify the dynamics of anthropometric characteristics of students during their studies at a specialized lyceum.
Keywords: physical development, monitoring, chest circumference, vital lung capacity, body weight